2022
DOI: 10.1186/s12885-022-09373-y
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in healthcare expenditures according to economic status in cancer patients undergoing end-of-life care

Abstract: Backgrounds A desire for better outcome influences cancer patients’ willingness to pay. Whilst cancer-related costs are known to have a u-shaped distribution, the actual level of healthcare utilized by patients may vary depending on income and ability to pay. This study examined patterns of healthcare expenditures in the last year of life in patients with gastric, colorectal, lung, and liver cancer and analyzed whether differences exist in the level of end-of-life costs for cancer care accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…A previous study also suggested an increased cancer burden in patients with HIV infection, and that the burden of non-AIDS-defining cancer would be increased and that of AIDS-defining cancer would be decreased due to aging and improved therapy for HIV infection [24]. In this study, the number of HIV patients with cancer was 235 in 2018 to Previous studies on the general population reported increased medical costs in the final months of the life of patients [16,[18][19][20]. In Korea, cost-sharing systems to reduce out-of-pocket medical expenses for cancer are available for five years after cancer diagnosis; hence, there are difficulties in estimating the medical cost of cancer after five years of diagnosis.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…A previous study also suggested an increased cancer burden in patients with HIV infection, and that the burden of non-AIDS-defining cancer would be increased and that of AIDS-defining cancer would be decreased due to aging and improved therapy for HIV infection [24]. In this study, the number of HIV patients with cancer was 235 in 2018 to Previous studies on the general population reported increased medical costs in the final months of the life of patients [16,[18][19][20]. In Korea, cost-sharing systems to reduce out-of-pocket medical expenses for cancer are available for five years after cancer diagnosis; hence, there are difficulties in estimating the medical cost of cancer after five years of diagnosis.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies on the general population reported increased medical costs in the final months of the life of patients [ 16 , 18 - 20 ]. In Korea, cost-sharing systems to reduce out-of-pocket medical expenses for cancer are available for five years after cancer diagnosis; hence, there are difficulties in estimating the medical cost of cancer after five years of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because economic accessibility can be improved by reducing patients' out‐of‐pocket burden. With the expectation of receiving high‐quality cancer treatment, patients desire to visit high‐volume or capital area hospitals from the perspective of medical use, resulting in an impact on overall cancer care such as excessive end‐of‐life medical expenditure 10–13 . According to the 2021 Health Insurance Review and Assessment statistics, more than half of cancer treatment medical costs occur in capital areas (62.4%).…”
Section: Introductionmentioning
confidence: 99%
“…With the expectation of receiving high‐quality cancer treatment, patients desire to visit high‐volume or capital area hospitals from the perspective of medical use, resulting in an impact on overall cancer care such as excessive end‐of‐life medical expenditure. 10 , 11 , 12 , 13 According to the 2021 Health Insurance Review and Assessment statistics, more than half of cancer treatment medical costs occur in capital areas (62.4%). Additionally, 68.2% of cancer‐related medical expenses are spent at tertiary hospitals.…”
Section: Introductionmentioning
confidence: 99%